1995
DOI: 10.21273/hortsci.30.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Using SPAD-502 Values to Assess the Nitrogen Status of Apple Trees

Abstract: Four apple (Malus domestica Borkh) cultivars (`Fuji', `Spartan', `Fiesta', and `Gala') on Malling 9 (M.9) rootstock were grown in the field with three N rates (5, 20, and 35 g N/tree per year), supplied as Ca(NO3)2, and fertigated daily for 9 weeks. In the second year, leaf SPAD readings (chlorophyll readings obtained with the Minolta-502 SPAD meter) increased over the growing season for all cultivars, and leaf N decreased. Leaf SPAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 14 publications
6
44
2
2
Order By: Relevance
“…Chang and Robison (2003) observed strong relationships between CCI and foliar nitrogen in four hardwood species. Neilsen et al (1995) observed significant correlations between CCI and foliar nitrogen concentration in four apple cultivars early, but not late, in the growing season. However, in a study that examined 12 red maple cultivars as a group, Sibley et al (1996) found no significant correlations between CCI and foliar nitrogen.…”
Section: Introductionmentioning
confidence: 79%
“…Chang and Robison (2003) observed strong relationships between CCI and foliar nitrogen in four hardwood species. Neilsen et al (1995) observed significant correlations between CCI and foliar nitrogen concentration in four apple cultivars early, but not late, in the growing season. However, in a study that examined 12 red maple cultivars as a group, Sibley et al (1996) found no significant correlations between CCI and foliar nitrogen.…”
Section: Introductionmentioning
confidence: 79%
“…Compared to more expensive extraction methods, the SPAD meter can rapidly estimate chlorophyll content (Azia and Stewart 2001;Madeira et al 2003;Yamamoto et al 2002). In plant nutrition studies, the SPAD meter has been successfully used to estimate nitrogen status in apple (Neilsen et al 1995), tomato (Sandoval-Villa et al 2002, red maple (Sibley et al 1996), and corn (Smeal and Zhang 1994) among other crops (Schepers et al 1998). Loh et al (2002) used a SPAD meter to quantitatively evaluate Populus deltoides foliage quality and calibrated the instrument based on chlorophyll and nitrogen content.…”
Section: Introductionmentioning
confidence: 99%
“…1). The Chl index (using the SPAD-502 meter) has been successfully used to assess the N status in apple trees (Neilsen et al 1995), grapevines (Porro et al 2001), hardwood tree species (Chang and Robinson 2003) and woody ornamental plants (Demotes-Mainard et al 2008). However, in most of such studies a simple linear regression was fitted to the data, which is different from our results.…”
Section: Resultsmentioning
confidence: 99%
“…The SPAD-502 portable Chl meter allows rapid, nondestructive measurements of the N status and the Chl content of leaves and has been tested in some major crops (Smeal and Zhang 1994, Neilsen et al 1995, Balasubra-Manian et al 2000, Porro et al 2001). …”
Section: Introductionmentioning
confidence: 99%